Children's Self-Esteem and Attitudes toward Disability, Perceived Competence and Morality: The Indirect Effect of Cognitive Empathy - Alexandra Maftei (MDPI AG, 2022)
The present study explored children's attitudes toward disability and the links with demographic factors (i.e., gender) and personal factors (i.e., empathy, sympathy, self-esteem). Our sample comprised 405 children aged 9 to 11 (M = 9.88, SD = 0.65, 47.4% males). First, we explored the links between self-esteem, empathy (cognitive and affective), and attitudes toward disability. Then, by using three scenarios involving a child in a wheelchair (Group 1), a child with an intellectual disability (Group 2), and a child with visual impairment (Group 3), we investigated the perceived competence and morality of these characters. The results suggested that cognitive empathy mediated the link between self-esteem and attitudes toward disability. Moreover, our data suggested that the character in a wheelchair (Group 1) received the highest scores regarding morality and competence, whereas the character with an intellectual disability (Group 2) received the lowest scores. We discuss the present findings regarding their practical implications for inclusive education strategies.